Horizontal axis wind turbine performance analysis - Asmuin, N.; B., Basuno; Nor Salim, N. A.; Ramli, M. F.; Ariffin, L. M.; Yaakub, M. F. (Penerbit UTHM, 2021)
The present work uses the method of Blade Element Momentum Theory as suggested by Hansen. The method applied to three blade models adopted from Rahgozar S. with the airfoil data used the data provided by Wood D. The wind turbine performance described in term of the thrust coefficient CT, torque coefficient CQ and the power coefficient Cp . These three coefficient can be deduced from the Momentum theory or from the Blade element Theory(BET). The present work found the performance coefficient derived from the Momentum theory tent to over estimate. It is suggested to used the BET formulation in presenting these three coefficients. In overall the Blade Element Momentum Theory follows the step by step as described by Hansen work well for these three blade models. However a little adjustment on the blade data is needed. To the case of two bladed horizontal axis wind turbine, Hansen’s approach works well over if the blade radius is RB the calculation should start from r = 0.1RB.